PERBANDINGAN LIFE SKILLS DENGAN CO-OP CO-OP DAN GROUP RESUME MEMPERHATIKAN KONSEP DIRI - Arrum Maishah Saba Putri; Edy Purnomo; Yon Rizal (JEE (Jurnal Edukasi Ekobis), 2015)
This research aims to confirm the difference of life skills among thestudents of VII grade at SMPN 1 Candipuro whose uses Co-op Co-op and GroupResume models by referring to the self-concept. The population in this research are112 students and the samples are 56 students. The result of research: (1) there is adifference of life skills between Co-op Co-op learning model with Group Resumelearning model on the subject of Integrated Social Science, (2) students life skillswhose uses Co-op Co-op learning model gain a higher than Group Resume learningmodel, both are applied for the students who have a high self-concept on the subjectof Integrated Social Science, (3) students life skills whose uses Co-op Co-oplearning model gain is lower than Group Resume learning model and both areapplied for students who have low self-concept on the subject of Integrated SocialScience, (4) there is an interaction between the learning models with the selfconcepttoward the life skills.Tujuan penelitian ini untuk mengetahui perbedaan life skills siswa kelasVII SMPN 1 Candipuro menggunakan model Co-op Co-op dan Group Resumedengan memperhatikan konsep diri. Populasi 112 siswa dan sampel 56 siswa. Hasilpenelitian: (1) terdapat perbedaan life skills antara model pembelajaran Co-op Coopdengan Group Resume pada mata pelajaran IPS Terpadu, (2) life skills siswapada model pembelajaran Co-op Co-op lebih tinggi dibandingkan dengan modelpembelajaran Group Resume bagi siswa yang memiliki konsep diri tinggi padamata pelajaran IPS Terpadu, (3) life skills siswa pada model pembelajaran Co-opCo-op lebih rendah dibandingkan model pembelajaran Group Resume bagi siswayang memiliki konsep diri rendah pada mata pelajaran IPS Terpadu, (4) terdapatinteraksi antara model pembelajaran dengan konsep diri terhadap life skills.Kata kunci: co-op co-op, group resume, konsep diri, life skills